Kedudukan Asset Yayasan Yang Dijadikan Jaminan Dalam Permohonan Kredit Bank - Rafnelly Rafki; Ahmad Muliadi; Irawan Santosa (Postgraduate of Jayabaya University, 2019)
The Foundation is a nonprofit organization incorporated under Article 1 paragraph 1 of Law No. 28 of 2004 on the amendment of Law 16 of 2001 on the Foundation. To be able to support in order to achieve his aim, the Foundation permitted to establish a legal entity and or participate in a business entity. This research is a descriptive analytical, research that provides data or description of the object of the research issues that are not intended to test the theory, but in the limit to explain the variable research on lending by banks to the foundation. In this research will be described regarding the granting of credit by banks to the foundation principles associated with healthy credit. The researches will provides answer that it can be seen that the intended use of foundation assets as collateral for the loan is membngun, expand, improve infrastructure facilities aimed at social, religious and humanitarian such as education and hospitals. If the foundations are in default or injury promises in the implementation of the payment and repayment of debt, the bank will carry out the execution of the foundation's assets used as loan collateral. The process of execution of loan guarantees its implementation in accordance with applicable laws similar position with the firm, CV, limited liability company and Cooperatives. In the execution of the foundation assets in case of default of payment execution carried out such a sum of money to the court decision binding. Execution starts with ends with auction rebukes and mortgage-burdened. After the auction the collateral objects and auction proceeds handed over to the lender, then the burden of mortgage objects will be handed over to the buyer diroya and auctions are clean and free of all expenses.